RISKS OF GINGER FARMING IN KUBU RAYA REGENCY (CASE STUDY IN TELUK EMPENING VILLAGE, TERENTANG DISTRICT) - As'ary, As'ary; Suyatno, Adi; Dolorosa, Eva; Rinaldi, Udin (Jurnal AGRISEP, 2022)
The purpose of this study was to analyze the income of ginger farming and to analyze the production risk and the risk of ginger farming income in Kubu Raya Regency. The research was conducted by survey based on qualitative descriptive method, data was taken directly using cross-sectional data. The selection of the research location was carried out purposively (deliberately) at the location of the horticultural farmer group. The research location is a farmer group in Teluk Empening Village, Terentang District, Kubu Raya Regency. The number of respondents as many as 131 members, are all members of the Empening Mandiri Gapoktan which consists of 6 groups from 15 existing farmer groups. The results of the study found several farming risks, consisting of income risk of 13% followed by production risk of 10.5% and price risk of 1.8%. The value of the coefficient of variation is less than 0.5, meaning that farmers are protected from the risk of loss and the RC ratio of 3.45 means that ginger farming is profitable to cultivate. The reality in the field is that the demand for fresh ginger is always increasing and production has not been fulfilled so that ginger farming is considered to be in accordance with farmers' expectations and is feasible to be developed.